Wild juvenile Dicentrarchus labrax L. liver antioxidant and damage responses at Aveiro Lagoon, Portugal - Maria, Vera L. (2020)
The Aveiro Lagoon, at the north-western coast of Portugal, has been under considerable anthropogenic pressure for the last 5 decades. In order to perform an adequate survey of the effects induced by the contaminants in presence, wild juveniles Dicentrarchus labrax (sea bass) were selected. Thus, sea bass was captured at five sites: Torreira (TOR, as reference site), Gafanha (GAF), Rio Novo Príncipe (RIO), Laranjo (LAR) and Vagos (VAG) in autumn 2005. Liver defence responses such as catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST), total glutathione (GSHt), total non-protein thiols (NP-SH) and metallothioneins (MT) were measured. Liver damage was determined as lipid peroxidation (LPO) and DNA integrity loss. RIO, LAR and VAG presented lower CAT, GR, GST activities and NP-SH and GSHt depletion in comparison to TOR. VAG and LAR showed higher GPx activity when compared to TOR. The highest MT level was found at GAF and VAG. The NP-SH and DNA integrity decreased at GAF compared to TOR. This field study demonstrated that not only antioxidant induction but also inhibitory responses must be considered as a signal of contamination.